The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/14651858.cd012572.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of antihypertensive drugs in older people

Abstract: Cochrane Database of Systematic Reviews Data collection and analysisWe compared the intervention of discontinuing or reducing antihypertensive medication to usual treatment using mean di erences (MD) and 95% confidence intervals (95% CIs) for continuous variables and we used Peto odds ratios (ORs) and 95% CI for binary variables. Our primary outcomes included: mortality, myocardial infarction, development of adverse drug reactions or adverse drug withdrawal reactions. Secondary outcomes included: blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 67 publications
(39 reference statements)
1
63
0
2
Order By: Relevance
“…No evidence was found regarding the benefits or harms of deprescribing blood pressure‐ or lipid‐lowering medication in people with diabetes. Recently, it was concluded that, for older people with diabetes in general, there is insufficient evidence to make firm conclusions about any positive or negative effects of discontinuing blood pressure‐lowering drugs 39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No evidence was found regarding the benefits or harms of deprescribing blood pressure‐ or lipid‐lowering medication in people with diabetes. Recently, it was concluded that, for older people with diabetes in general, there is insufficient evidence to make firm conclusions about any positive or negative effects of discontinuing blood pressure‐lowering drugs 39 …”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was concluded that, for older people with diabetes in general, there is insufficient evidence to make firm conclusions about any positive or negative effects of discontinuing blood pressure-lowering drugs. 39 Eligibility criteria for deprescribing varied among the studies but usually included HbA 1c or systolic blood pressure levels below a certain level and/or being at high risk of adverse events. There is still debate about the eligibility criteria for deprescribing.…”
Section: Discussionmentioning
confidence: 99%
“…A growing interest in deprescribing in older multimorbid patients has been fuelled by mounting evidence on the potential harms of polypharmacy over the last two decades (11)(12)(13)(14)27), as evidenced by the changes in the QOF (8). However, these trends have yet to translate into specific guidelines that would equip GPs for stopping preventive medication with the degree of confidence with which they prescribe it (17,31).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Relevant 'brief reading' includes recommendations on how to recognise and action opportunities for deprescribing (23)(24)(25) and NICE guidance on multimorbidity, none of which offers advice on reducing specific groups of medication, including antihypertensives (26). These reflect the lack of current evidence about the advantages of withdrawing antihypertensive medication (5,12,13,27).…”
Section: Introductionmentioning
confidence: 99%
“…This study described in this protocol aims to look at the safety and efficacy of cardiovascular medication reduction compared to usual care in patients aged 75 years and over. There are existing systematic reviews that examine the clinical outcomes of reducing cardiovascular drugs, but these provide insufficient evidence to support clinical decision making [ 15 18 ]. One systematic review focused on the clinical outcomes of the medication reduction intervention itself, without evidence for the effect of individual drug classes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%